HUBUNGAN PENGETAHUAN, SIKAP, MOTIVASI DAN DUKUNGAN KELUARGA DENGAN KUNJUNGAN IBU NIFAS DALAM PEMERIKSAAN PASKA BERSALIN DI WILAYAH KOTA SEMARANG TRIWULAN II TAHUN 2017 - Santi Tri Rahayu; Farid Agusyahbana; Atik Mawarni; Djoko Nugroho (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Maternal mortality is most common in the puerperium (74.29%). Postpartum maternal deaths can be prevented postpartum care. The Coverage of postpartum visits to the 3 (KF3) is the lowest in Health Center Ngemplak Simongan (59.93%), Padangsari (62.07%), and Tlogosari Kulon (66.89%), not yet meet the target of health services (90%). The aim of research to analyze behavioral factors and family support with a visit of mother postpartum in postpartum examination. Type of research explanatory research with cross sectional study design. The population in this study is the mother postpartum period of KF3 in Tlogosari Kulon, Ngemplak Simongan, and Padangsari number of 114 postpartum mothers and samples were taken by simple random sampling technique of 88 postpartum mothers. The data analysis used univariate, bivariate using Spearman rank and multivariate using linear regression. The results of study showed that not knowing about postpartum examination(50%), have attitude agree but check only when there is complaint (33%), have good motivation but check if health care officer (47,7%), get familly support but of husbands or families did not get examination on KF3 (59,1%). Analysis shows there was a correlation between attitude(p=0.038; rs=0.22) and the support of her husband (p=0.028; rs=-0.234) with the visit of postpartum mothers. Variabel knowledge (p=0,289), motivation (p=254), dan family support (p=0,187) were not correlation to visit of postpartum mothers. There is the influence attitudes with the visit postpartum mothers (p=0.005, t=2,894; CI=0,053-0,285). It is recommended that midwives should improve their knowledge, attitude, motivation and family support from postpartum with discussion and interpersonal communication.